Dystocia as a cause of untimely cesarean section - Đuric Janko; Arsenijevic Slobodan; Bankovic Dragic; Protrka Zoran; Sorak Marija; Dimitrijevic Aleksandra; Tanaskovic Irena (Vojnosanitetski Pregled)
Background/Aim. One of the most frequent indications for cesarean section is dystocia. It is impossible to predict, difficult to identify and coincident with the rapid expiry of the expected time, so it is important to point out some mistakes in expecting vaginal delivery. The aim of this study was to examine the frequency and the length of dystocia-related cesarean delivery, as well as the vitality of the newborn immediately after birth. Methods. A prospective, 3-year study was conducted including a total number of 6,470 deliveries regardless of whether they were completed using cesarean section after an unsuccessful attempt of spontaneous vaginal delivery or not. The Apgar score, a proved useful tool for the assessment of the vitality of newborn children in the first minute, was used. Results. On the basis of the established indications, 653 (10.10%) of deliveries were completed using cesarean section. Dystocia was the third most common indication for cesarean section (16.38%). Deliveries in which dystocia was established as a diagnosis lasted much longer (p = 0.030) which resulted in weaker vitality of newborn children (p = 0.000) compared to the deliveries ended by spontaneous vaginal delivery. Conclusion. This study shows that deliveries caused by dystocia last much longer and newborn children are of weaker vitality compared to other deliveries caused not by dystocia. Decisions concerning cesarean section must be made in a timely fashion.